Genetic analysis of the tetA(C) gene on plasmid pBR322. - McNicholas, P (1992)
The TetA(C) protein, encoded by the tetA(C) gene of plasmid pBR322, is a member of a family of membrane-bound proteins that mediate energy-dependent efflux of tetracycline from the bacterial cell. The tetA(C) gene was mutagenized with hydroxylamine, and missense mutations causing the loss of tetracycline resistance were identified at 30 distinct codons. Mutations that encoded substitutions within putative membrane-spanning alpha-helical regions were scattered throughout the gene. In contrast, mutations outside the alpha-helical regions were clustered in two cytoplasmic loops, between helices 2 and 3 and helices 10 and 11, suggesting that these regions play a critical role in the recognition of tetracycline and/or energy transduction. All of the missense mutations encoded a protein that retained the ability to rescue an Escherichia coli strain defective in potassium uptake, suggesting that the loss of tetracycline resistance was not due to an unstable TetA(C) protein or to the failure of the protein to be inserted in the membrane. We postulate that the mutations encode residues that are critical for the active efflux of tetracycline, except for mutations that result in the introduction of charged residues within hydrophobic regions of the TetA(C) protein.